2008
DOI: 10.1016/j.addbeh.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Empirically supported substance abuse treatment approaches: A survey of treatment providers' perspectives and practices

Abstract: To better understand the extent that empirically supported and promising substance abuse treatment approaches are implemented in community settings, treatment providers were surveyed regarding their perceptions and use of several psychosocial and pharmacological treatment interventions. Program directors (n=30) and staff members (n=331) from diverse community settings rated the effectiveness and extent of use of various treatment interventions, and provided information on program and workforce characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 33 publications
(36 reference statements)
2
84
1
Order By: Relevance
“…Long-term treatment strategies, including medication, psychological counseling, and community-based programs, are important in the management of drug dependency. 521,535 There is insufficient evidence to evaluate the clinical utility of screening tests for drug abuse in primary care settings, including toxicology tests of blood or urine, or the use of standardized questionnaires to screen for drug use or misuse. 536…”
Section: Drug Abusementioning
confidence: 99%
“…Long-term treatment strategies, including medication, psychological counseling, and community-based programs, are important in the management of drug dependency. 521,535 There is insufficient evidence to evaluate the clinical utility of screening tests for drug abuse in primary care settings, including toxicology tests of blood or urine, or the use of standardized questionnaires to screen for drug use or misuse. 536…”
Section: Drug Abusementioning
confidence: 99%
“…This model requires that the rewards be of value to the client and increase in value as the length of non-use of drugs continues. This method is considered expensive (Hart et al, 2009) and has been reported by therapists in the field to be the least effective of the previously described therapies (Herbeck, Hser, & Teruya, 2008).…”
Section: Strategy/interventionmentioning
confidence: 98%
“…Because of a lack of capacity to treat in 28 day hospitals and mental health clinics, clinicians decided to implement the Matrix model [20]. The Matrix model incorporates evidence-based practices to effectively help individuals struggling with dependence issues to begin alleviating those issues with acquired skills.…”
Section: The Matrix Modelmentioning
confidence: 99%
“…The Matrix model incorporates evidence-based practices to effectively help individuals struggling with dependence issues to begin alleviating those issues with acquired skills. Components of the program include individual sessions, early recovery groups, relapse prevention groups, family education sessions, 12 step meetings, social support groups, relapse analysis and urinalysis [20].…”
Section: The Matrix Modelmentioning
confidence: 99%